PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) TERHADAP MOTIVASI BELAJAR SISWA KELAS IV SD NEGERI 09 SITIUNG - Estika Hader, Antik; Salahuddin, Amar; Oktari, Sindi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Student Teams Achievement Divisions (STAD) cooperative learning model on the learning motivation of fourth-grade students at SD Negeri 09 Sitiung. The background of this research is the low learning motivation of students during the learning process, where students tend to be passive and less enthusiastic about learning. This research uses a quantitative approach with a Pre-Experimental Design and a One Group Pretest-Posttest Design. The population and sample consisted of 9 fourth-grade students using saturated sampling. The data collection instrument was a learning motivation questionnaire that had been validated by experts. Data analysis was performed using the Shapiro-Wilk normality test and the Paired Sample T-Test with the help of SPSS 20. The results showed that the average pretest score was 58.44 and the posttest score was 72.33, with an increase of 13.89 points. The hypothesis test obtained a Sig. (2-tailed) value of 0.029 < 0.05, meaning H₀ is rejected and Hₐ is accepted. It is concluded that the STAD cooperative learning model has a significant effect on the learning motivation of fourth-grade students at SD Negeri 09 Sitiung.